Radiation stimulated violations of magnetic order in the fe-be layered system irradiated by krypton ions - Ozernoy, A.N.; Vereshchak, M.F.; Manakova, I.A.; Shokanov, A.K.; Rusakov, V.S.; Kadyrzhanov, K.K. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
Studies of structural and phase state of Be-Fe-Be three-layer system were conducted using Mössbauer spectroscopy method at 57Fe nuclei after krypton ions irradiation with energy of 280 keV and subsequent isochronous annealing. Under irradiation, a local concentration of beryllium atoms was observed in the subsurface layer of the layered system samples. This concentration causes transition of a substantial part of the Fe atoms in the subsurface layer from a magnetic ordered state to the paramagnetic one. Post-radiation isochronous annealing results in almost complete recovery of pre-implantation local concentration of components and restoration of structure of the irradiated subsurface layer. Presented in the paper experimental results show that the implanted krypton has a great impact on the phase state of the layered system, and they can be useful to better understand and predict the effects of the gas discharge in neutron fields on radiation effects in structural materials of nuclear and thermonuclear facilities.
Keywords: Mössbauer spectroscopy; subsurface layer; layered system; irradiation